Single‐cell heterogeneity in suppression of PC12 differentiation by direct microinjection of a differentiation inhibitor, U0126. (20th May 2014) - Chung, Jihye; Miura, Natsuko; Ito, Akio; Sawada, Munetaka; Nishikawa, Shigemichi; Kuroda, Kouichi; Ueda, Mitsuyoshi
Abstract Phenotypic and genomic heterogeneity among single cells in a cell population leads to inaccuracy and obscuration in research about mammalian cell differentiation. In order to address the problems regarding bulk analysis on heterogeneous cell populations, it is necessary to accurately regulate and analyze changes in differentiating cells at the single‐cell level. To investigate the single‐cell changes in PC12 neuronal differentiation that occur when inhibited by U0126, an inhibitor of mitogen‐activated protein kinase kinase (MEK), we directly injected the chemical into individual target cells and analyzed the outcomes (neurite outgrowth) at the single‐cell level. As a result, we could accurately regulate the quantity of U0126 being introduced into each target cell, which was previously not possible using the common method of simply adding the inhibitor to the culture medium. It was possible to analyze the inhibitive effect of U0126 even when the injected quantity was lower than the lower limit for inhibition when added to culture medium (0.1 μM, identical to 1.2 × 108 molecules per cell on dish). In particular, injection of 1.5 × 107 molecules into each cell resulted in a 59% decrease of the mean total neurite length. Time‐course analysis of neurite outgrowth at the single‐cell level using fluorescence staining method showed that the changes in neurite length of differentiating PC12 cells were not homogeneous, but were largely variable across individual target cells.